Identifying the Mechanical Parameters of Hard Coating with Strain Dependent Characteristic by an Inverse Method - Wei Sun; Zhuo Wang; Mingwei Zhu; Guangyu Du (Shock and Vibration)
The mechanical parameters of hard coating, such as storage modulus and loss factor, are affected by preparation technology significantly and have the strain dependent characteristic. So the effective identification of these mechanical parameters becomes a challenge task. In this study, a hard-coating cantilever thin plate under base excitation was taken as the research object, and an inverse method was developed to identify these mechanical parameters. Firstly, the principles of identifying storage modulus and loss factor of hard coating were presented according to the inverse method. Then, from the need of parameters identification, the analytical model and calculation formula of equivalent strain for the hard-coating composite plate were derived. Next, also for parameter identification, the vibration experiments about the cantilever plate coated with NiCoCrAlY+ yttria-stabilised zirconia (YSZ) hard coating were performed. Finally, the mechanical parameters of NiCoCrAlY+YSZ hard coating with strain dependent characteristic were identified by the proposed method. The identification results show that the change rules of storage modulus and loss factor of hard coating with the strain amplitude are almost consistent with the results listed in the other similar references. However, the identification results herein can more directly serve for the dynamic modeling of hard-coating plate-shape composite structure.